Development of an iron-metal organic Framework-based dispersive solid phase extraction coupled with flame atomic absorption spectrophotometry for the accurate and sensitive determination of copper in lion's claw tea samples - Teki̇n Semerci, Zeynep; Karakebap, K. Übra; Nur Karaman, Devrim; Yilmaz, Eylül; Dalgiç Bozyi̇ği̇t, Gamze; Er, Elif Öztürk; Bakirdere, Sezgin (Royal Society of Chemistry (RSC), 2025)
An iron-based metal organic framework (Fe-MOF) constructed using terephthalic acid as an organic linker was synthesized and characterized for its implementation in a dispersive solid-phase extraction (dSPE) procedure.
Keywords: Tea; Limit of Detection; Spectrophotometry, Atomic; Iron; Solid Phase Extraction; Copper; Metal-Organic Frameworks